The Effect of Alternative Pruning Methods on the Viticultural and Oenological Performance of Some Wine Grape Varieties - Archer, E.; van Schalkwyk, D. (South African Journal of Enology and Viticulture, 2016)
Three different trials, at three different localities, each with different growing conditions, were conducted with nine different wine grape varieties. Four different pruning methods, hand, mechanical, minimal and no pruning were tested. Growth responses, grape composition and morphology, wine quality as well as labour inputs were evaluated. Huge labour savings were obtained with the alternative pruning methods compared to hand pruning. A reduction in vigour and increase in yield were evident in each variety. Wine quality was not decreased and in some cases even a quality increase was evident. Varieties differ in their adaptability to alternative pruning methods with Cabernet Sauvignon, Pinotage and Chardonnay performing well and Sauvignon blanc and Merlot poorly. Chenin blanc, Shiraz, Colombar and Ruby Cabernet showed acceptable performance. Alternative pruning methods proved to be viable, especially for the production of medium and low priced wines.